2014
DOI: 10.3846/20294913.2013.880080
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Disciplinary Knowledge: Desperate Call From Business Enterprises in Coming Smart Working Era

Abstract: Science and technology is critical for execution and operations of modern businesses. As business operations consists of purposeful execution of technologies with appropriate social cooperation and coordination, knowledge in use is actually cross-disciplinary irrespective of domain or discipline of business. As information technology infiltrates today's businesses, people would need to work smarter using technologies including information technologies. This study explores executives' perceptions of cross-disci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Sony (2020) emphasized the crucial role of science and technology in the execution of Industry 4.0 and operation service 4.0. Lee (2013) explained that current businesses are replete with information technology, and individuals must work smarter than before with the aid of technologies, including information technology. Moreover, a robust portable system already exists because of the sudden and drastic acceleration in the blooming and diffusion of emergent technologies that assist social networking, communication and collaboration with the permeating dispersal of potent and user-friendly mobile devices (Ahuja et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sony (2020) emphasized the crucial role of science and technology in the execution of Industry 4.0 and operation service 4.0. Lee (2013) explained that current businesses are replete with information technology, and individuals must work smarter than before with the aid of technologies, including information technology. Moreover, a robust portable system already exists because of the sudden and drastic acceleration in the blooming and diffusion of emergent technologies that assist social networking, communication and collaboration with the permeating dispersal of potent and user-friendly mobile devices (Ahuja et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the works of Lee [15], de Sousa Jabbour et al [16], and Kryshtanovych et al [17] the specifics of the SMART management system were considered but we focused on how SMART management can contribute it is sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, very similar challenges were identified when was investigated the impact of courses trained to the staff members, also in industry. Science and technology delivered in a cross-disciplinary manner and the sequence of relevant training courses were considered essentially for business activities success in a research reported by Lee (2013) and conducted in Seoul, Korea.…”
Section: Curriculum Assessment Automation -Context Requirementsmentioning
confidence: 99%